Engineering cartilage graft using mesenchymal stem cell laden polyacrylamide-galactoxyloglucan hydrogel for transplantation. (September 2021) - Gopalakrishnan Usha, Preethi; Jalajakumari, Sreekutty; Sheela, Unnikrishnan Babukuttan; Mohan, Deepa; Berry, Catherine; Tripathi, Anuj; Thankappan Nair, Sreelekha T
Hydrogels are reported to have various biomedical field applications, and many reports also suggest that soft gels promote stem cell differentiation. Chondrogenic differentiation of mesenchymal stem cells (MSC) is significant in articular cartilage repair. This study focuses on polysaccharide-based hydrogels which enhance chondrocyte lineage differentiation of MSC when grown in the hydrogels. This study implies that the prepared hydrogels promote specific lineage without any external chemical induction factors. The techniques, including immunofluorescence and functional assays to assess the differentiation and in vivo implantation, were employed. All observations paved the way towards confirmation that the galactoxyloglucan-based hydrogel is an attractive candidate for supporting stem cell growth and cartilaginous differentiation.